The Importance of Local Sustainable Food Systems in Ensuring Food Security - Mičović, Elizabeta (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
Ensuring sufficient amounts of safe, high-quality food accessible to all is the foundation of food security and public health. The importance of local sustainable food systems, short supply chains, and self-sufficiency in healthy food is also emphasised by both the Common Agricultural Policy and the Nutrition Policy. Timely management of all identified risks, especially during crises that threaten food security, strengthens local sustainable food systems. Cooperation among stakeholders in the food chain - food producers, the food-processing industry, retailers, mass caterers, responsible authorities, and consumers - plays a key role. Increased consumption of local products and goods also creates new jobs and supports the preservation and development of rural areas and their communities. The paper highlights the importance of local sustainable food systems and their impact on food security and self-sufficiency in Slovenia. It focuses on challenges, potential risks, and corrective measures for risk management, aimed at improving conditions.